A novel energy-economic-environmental evaluation model for heat pump air conditioners integrated with waste heat recovery in electric vehicles. (January 2023) - Yu, Xiaoli; Jiang, Ruicheng; Lu, Guodong; Liu, Hao; Tong, Yuxiang; Qian, Gao; Huang, Rui; Li, Zhi
Abstract: Heat pump air conditioners (HPAC) have been widely investigated in electric vehicles (EVs) due to their high efficiency and energy-saving advantages, but the energy performance of HPAC deteriorates significantly under low-temperature weather conditions. In recent years, heat pump air conditioners combining waste heat recovery (HPAC-WHR) systems have been proposed to improve the energy efficiency of HPAC and mileages of EVs, by utilizing the waste heat of batteries, motors and motor controllers. However, effects of the WHR subsystem on the energy, economic and environmental performance have not been considered before, and there is a lack of unified evaluation criteria for different HPAC-WHR systems. Therefore, a novel evaluation model is proposed for HPAC-WHR systems in this study, and the energy, economic and environmental performance of typical HPAC-WHR systems are comprehensively evaluated and compared, providing theoretical guidelines for future design and optimization of more efficient HPAC-WHR systems in EVs. Results based on the proposed evaluation model indicate that the condenser-side HPAC-WHR system possesses the best comprehensive performance when the ambient temperature is low and the quantity of waste heat is small, while the refrigerant-side HPAC-WHR system achieves the best comprehensive performance under high ambient temperature and large quantity of waste heat. By combining the advantages of the condenser-side and refrigerant-side systems, a novel HPAC-WHR system is designed and its performance is compared with the refrigerant-side system. The comparison results demonstrate that the novel system outperforms 18.9% higher in COPcom and 14.7% lower in life-cycle carbon emissions, with only 2.1% increase in comprehensive cost.